Influence Of System Quality, Information Quality, And Service Quality On User Satisfaction And Use Of The Staffing Service Application System In Employees In Bengkulu Central District - Ivone, Lidya Christina (UNIB Press, 2023)
This study aims to examine the effect of System Quality on User Satisfaction, examine the effect of System Quality on User Satisfaction, examine the effect of Information quality on User Satisfaction, test the effect of Information quality on User Satisfaction and test the effect of Service quality on User Satisfaction and test the effect of Service Quality on Application System User Satisfaction. Staffing Services to Bengkulu Regency employees. This type of research is survey research. The sample in this study was taken by random sampling which was distributed to employees in 40 regional apparatus organizations in Central Bengkulu Regency. To see the effect between variables using Smart PLS by testing the outer model and inner model. The results of the study found that the quality of the system has a significant influence on usage and the relationship between the two is positive, the quality of the system has a significant effect on user satisfaction and the relationship between the two is positive, the quality of information has a significant influence on the use and the relationship between the two is positive, the quality of information has a significant influence on User Satisfaction and the relationship between the two is positive, and Service Quality has a significant influence on Use and the relationship between the two is positive and Service Quality has a significant influence on User Satisfaction of the Personnel Service Application System for Central Bengkulu Regency employees and the relationship between the two is positive .